2009
DOI: 10.1007/s10661-009-1194-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of heavy metal sources by multivariable analysis in a typical Mediterranean city (SE Spain)

Abstract: Problems associated with heavy metal characterization in the majority of sites are often due to multiple sources of pollution. This work presents the results through the use of advanced statistical techniques to identify sources of soil heavy metals in a typical Mediterranean city. The multivariable analysis performed on seven metals identified four sources controlling their variability. Cr, Mn, and Ni contents were associated to soil parent materials; Cd and Pb contents were related to anthropogenic activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 52 publications
4
29
0
1
Order By: Relevance
“…Heavy Metals (Cd, Cr, Cu, Zn, Mn, Pd, and Al) Although, with no statistical significance, the registered variations on Chromium, Cadmium, Copper, Nickel and Lead demonstrate an increasing tendency during the first three years of the assay, after which they decrease and stabilize. These changes in heavy metals content are in line with the consulted literature [23,40,[62][63][64][65]. Furthermore, the obtained results (low levels of heavy metals recorded and non-significant evolution of this parameter over time) were along with the expectations, considering both the characteristics of the study area (a natural landscape free of pollution incidents, with very low levels of industrialization), and the implemented cultural system in which the amount of fertilizers and phytosanitaries applied is very low [29,54].…”
Section: "Available" Phosphorus and Potassiumsupporting
confidence: 89%
“…Heavy Metals (Cd, Cr, Cu, Zn, Mn, Pd, and Al) Although, with no statistical significance, the registered variations on Chromium, Cadmium, Copper, Nickel and Lead demonstrate an increasing tendency during the first three years of the assay, after which they decrease and stabilize. These changes in heavy metals content are in line with the consulted literature [23,40,[62][63][64][65]. Furthermore, the obtained results (low levels of heavy metals recorded and non-significant evolution of this parameter over time) were along with the expectations, considering both the characteristics of the study area (a natural landscape free of pollution incidents, with very low levels of industrialization), and the implemented cultural system in which the amount of fertilizers and phytosanitaries applied is very low [29,54].…”
Section: "Available" Phosphorus and Potassiumsupporting
confidence: 89%
“…All the available heavy metal concentrations were positively correlated with pH. This last result was unexpected because most of the literature consulted describes an increase in pH as leading to a decrease in the available heavy metal content [58,59]. This might be because increased pH's could thus favor the release of these metals by mobilizing the soil components in which they are retained.…”
Section: Correlation Analysismentioning
confidence: 91%
“…Moreover, the observed differences in the range of metals are most likely caused by variation in the sources of the metals. Acosta et al 21 identified industrial activities and traffic as the main sources of Pb while Cu was associated with inorganic fertilizers in agricultural areas, and Zn was related to recreational, domestic, and commercial sources. Adachi and Tainosho 22 from their studies on the morphology and chemical composition of heavy metals embedded in tyre dust and traffic related materials, concluded that tyre dust is a significant pollutant, especially as a source of Zn in the urban environment.…”
Section: Heavy Metals In Bulk Samplesmentioning
confidence: 99%